A Computational Validation of Water Molecules Adsorption on an NaCl Surface - Xiao-Yan Liu; Jing-Wen Cao; Xiao-Ling Qin; Xu-Liang Zhu; Xu-Hao Yu; Xue-Chun Wang; Xiao-Qing Yuan; Yu-He Liu; Yong Wang; Peng Zhang (Crystals, 2021)
It was reported that a scanning tunneling microscopy (STM) study observed the adsorption geometry of a water monomer and a tetramer on NaCl(100) film. Based on first-principles density functional theory (DFT), the adsorption behavior of water on the NaCl surface was simulated with CASTEP code. The results showed that the water monomer almost lay on the NaCl(001) surface with one O–H bond tilted slightly downward. This was quite different from the STM observations. In fact, the experimental observation was influenced by the Au(111) substrate, which showed an upright form. A recent report on observations of two-dimensional ice structure on Au(111) substrate verified our simulations. However, the water tetramer formed a stable quadrate structure on the surface, which was consistent with observation. The intermolecular hydrogen bonds present more strength than surface adsorption. The simulations presented a clearer picture than experimental observations.